Streamline Monohull Ship Form For Sea-High Speed Crafts - Wenehenubun, Frederikus (Cylinder : Jurnal Ilmiah Teknik Mesin, 2019)
Sea transportation for many inhibited small islands with no transportation link to market and education center is one of the most concern for economic growth. A good reliable hull form for fast marine vehicles carrying passengers, car, and goods has been defined. The design process was to apply the concept of monohull and frigate form for good seakeeping and structural strength considering wavy Indonesian water. Smiplaning hull form was introduced to meet the criteria of fast marine vehicles and take into account streamline hull surface, fluid flow, total resistance in calm water were studied by towing tank model tests. Variation of waterline entrance angles as the main variable result good performance of 9.50 angle hull form more than the two others 6.50 angle and 110 angle. Sectional area dan breadth ratios to their maximum values were prepared. This as means for preliminary design and further study of the hull form.